Recyclable and Reusable Natural Plant‐Based Paper for Repeated Digital Printing and Unprinting. Issue 19 (5th April 2022) - Zhao, Ze; Deng, Jingyu; Tae, Hyunhyuk; Ibrahim, Mohammed Shahrudin; Suresh, Subra; Cho, Nam‐Joon
Abstract: Although paperless technologies are becoming ubiquitous, paper and paper‐based materials remain one of the most widely used resources, predicted to exceed an annual total of 460 million metric tons by 2030. Given the environmental challenges, deleterious impact on natural resources, and waste associated with conventional wood‐based paper manufacturing, developing more sustainable strategies to source, produce, and recycle paper from natural materials is essential. Here, the development and production of reusable and recyclable paper are reported. This approach offers a pathway for easily producing natural pollen grains via ecofriendly, economical, scalable, and low‐energy fabrication routes. It is demonstrated that the pollen‐based paper exhibits high‐quality printability, readability, and erasability, enabling its reuse. Based on the pH‐responsive morphological responses of engineered pollen materials, a method for hygro stable printing and on‐demand unprinting is presented. The reusability of the pollen paper renders it more advantageous than conventional single‐print wood‐based paper. This study thus provides possible pathways to utilize non‐allergenic pollen, which is renewable and naturally abundant, as a sustainable source of reusable paper. While this work primarily deals with paper, the methods described here can be extended to produce other products such as cartons and containers for the storage and transport of liquid and solid materials. Abstract : An eco‐friendly and in situ recyclable alternative to current wood‐derived printing paper is reported. The novel paper is fabricated from renewable plant pollen quickly and straightforwardly with less energy consumption and shows excellent printability, readability, and pH‐triggered ability of toner erasability. Repeated reprinting and recycling are demonstrated due to their stable hydroswelling property.